Consistency paradox revisited. A procedure for estimating interindividual consistency independently from the measure - José Manuel Hernández; Victor J. Rubio; José Santacreu; Javier Revuelta (Análisis y Modificación de Conducta, 2025)
Mischel (1968) argued against the idea of a general consistency of human beings.